Visualising mechanics: washing machine dynamics. Issue 4 (21st April 2021) - Cumber, Peter
Abstract : Mechanical engineering students often find the formulation and analysis of dynamical systems difficult. The response of some mechanical engineering undergraduates is that as much as possible courses on mechanics are best avoided. The aim of this paper is to produce some interesting dynamical systems that may help to change the opinions of the students. A dynamic model for the washing in a washing machine and the washing machine are presented. At mid-range, spin speeds the washing machine slides across the ground and at higher spin speeds; the washing machine both slides and rocks from side to side. The models are formulated using concepts taught in the early years of an undergraduate course in mechanics and where appropriate simplifying assumptions are made to ensure it is a realistic goal for undergraduate students to understand the model basis. This allows a student's focus to be on the influence of different parameters on the system dynamics. The simulation tool could be used as a dynamics demonstrator in a lecture or as an educational tool driven by the imagination of the student. In this paper, several simulations are presented and analysed.